Determinant of Overload Occurrence in Clients Chronic Kidney Failure with Hemodialysis - Tri Mochartini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Patients with renal failure who are in the final stage require replacement therapy for kidney function to maintain their survival such as kidney transplantation, hemodialysis and Continuous Ambulatory Peritoneal Dialysis (CAPD) therapy. Failure of kidney function can cause overload complications. In order to avoid complications from overload, good precautions must be taken, namely adherence to limiting fluid. Compliance must be based on the level of knowledge of the individual itself. The higher the level of knowledge is more open by carrying out compliance in limiting fluid in chronic renal failure with hemodialysis. Main Objectives: Knowing the Determinants of Overload Occurrence in Chronic Kidney Failure with Hemodialysis at the Indonesian Christian University Hospital in 2019. Research Method: Analytical Method, the sample in this study were all chronic renal failure patients who performed routine hemodialysis in the UKI Hemodialysis Hospital in February 2019 and the instruments used in this study used a questionnaire of 56 respondents. So the sampling method in this study is incidental sampling. Results: From the results of the Chi Squere test, the researchers obtained p-value <0.05, meaning that there was a relationship between age, type, sex, education, duration of hemodialysis, knowledge and adherence to overload. Suggestion: It is expected that health workers in the HD room of the Christian University Hospital will provide knowledge to clients and families through routine counseling and education about overloaded kidney failure and risks if they do not comply with fluid restrictions. If the client has knowledge about overload, the liquid compliance will be greater.